LABORATORY EXPERIMENTAL RESEARCH OF LOADING FORCES DEVELOPMENT ACTING ON THE SIDE SURFACE OF THE PILES - Naydenova, V. E. (Academic journal Industrial Machine Building Civil Engineering, 2018)
The forces of negative friction or loading forces of friction on the piles develop due to additional deformations of near pile array and they cannot be more force of resistance on the side of pile in rest, that is formed due to own weight of the ground founding. The paper presents the results of laboratory experimental research of loading forces of friction acting on the lateral surface of the piles without taking into account the vertical load (being relatively at rest) and provided an analysis of methods for detection of negative friction forces (loading forces) acting on the lateral surface of the pile, with the appointment of their load-bearing capacity. The researches have confirmed the theoretical statement about the equality of the loading forces of friction to ground resistance forces under the action of the torque load but not the pulling load, as it is suggested in the modern standards.